Tertiary Students’ Perceptions on Spotify Application In Improving English Pronunciation - nazriani lubis; Putri Anjani (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2022)
Listening music through music streaming has become part of tertiary students’ activities. Music streaming is one of the media that can improve students' English pronunciation. The purpose of this research was to investigate three students’ perceptions from different Universities in Indonesia on the use Spotify application in improving English pronunciation. A qualitative research method with thematic analysis was applied in this research and the subjects of this research were three students; one English student and two non-English students, based on the parameter of the feature of Spotify, namely; the students’ interest and the students’ motivation (Andriani et all, 2018; Rahmania & Mandasari, 2021). Three themes were found on the interview, namely; Accessible and Flexible Feature, Interesting Media for Learning and Practicing English Pronunciation. The results of this research revealed that the use of Spotify feature on the English pronunciation of all participants increased the students’ pronunciation, particularly in terms of word and meaning. Two non-English students did not pay attention to the elements of English pronunciation; vowel, stress, rhythm, pitch and intonation. However, only English students pay more attention and more comprehensive elements of English pronunciation. It proves that educational background had an effect on improving students’ pronunciation